Consumer Movements Confronted by Naturalness in Gene Editing in Japan. Issue 1 (2nd January 2021) - Otsuka, Yoshiki
Abstract: This study describes consumer opposition toward genetically modified organisms (GMOs) in Japan in response to gene editing technology that may not be subjected to the Cartagena Act regulating GMOs, since edited organisms cannot be distinguished from naturally occurring ones. The notion of naturalness, criticized as unscientific in the past, has become a scientific reason to exempt gene editing from regulations. Qualitative research of three consumer organizations and text analysis of public comments to the Ministry of the Environment confirmed the emergence of naturalness in the discursive space between experts and consumers. Consumer movements define naturalness as the lack of artificial manipulation, while experts define it according to its similarity to nature. Additionally, a questionnaire survey of consumers who attended consumer organization meetings was conducted and analyzed to understand different perceptions of naturalness and gene editing technology. Perceptions of gene editing and naturalness negatively correlated with those of conventional crossing, contrary to the recognition of experts, suggesting that consumer perception of naturalness differs. Moreover, anticipated attitudes toward gene editing were shown to be significantly influenced by present attitudes toward GMOs, although the perceived naturalness of gene editing is independent of GMOs.